A fenntartható fogyasztás iránt elkötelezett fogyasztók megjelenése Magyarországon - Rácz, Georgina; Horváth, Ágnes (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
Nowadays the significance of the concept of sustainable consumption is getting harder, which assumes the appearance of the conscious consumers. In the first part of this study based on international literature we introduce the main behavioural characteristics of the LOHAS, and according to the domestic literature we examine the relevance of the LOHAS concept in Hungary. In the second part results of a research (conducted within the framework of a country level representative data collection) carried out in September, 2011 by Cognative Ltd. are being introduced, which shows that values on the path of sustainability have also appeared in Hungary. Finally we pointed out that the trend follower consumer groups in Hungary assign new market opportunities and risks for companies with homogenous products.